2014
DOI: 10.1089/gtmb.2013.0491
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variation of Sodium Taurocholate Cotransporting Polypeptide with Chronic Hepatitis B Virus Infection

Abstract: Background: Sodium taurocholate cotransporting polypeptide (NTCP) plays an important role in the enterohepatic circulation of bile acids and hepatocyte function and was recently proposed to be a functional receptor for hepatitis B virus (HBV). Objective: This study investigated the association of the functional polymorphism c.800C > T (p.S267F) (rs2296651) of the NTCP gene with HBV infection. Methods: The study included 244 patients with chronic HBV infection, 76 HBV infection resolvers, and 113 healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 22 publications
2
50
2
1
Order By: Relevance
“…Host genetics significantly contributes to the clinical outcome of HBV infection. NTCP plays an important role in the enterohepatic circulation of bile acids and also serves as a receptor for hepatitis B and D viruses . However, a previous study has reported that common variants in NTCP might not influence the expression level of SLC10A1 at transcriptional regulation, hence may not be associated with HBV susceptibility .…”
Section: Introductionmentioning
confidence: 98%
“…Host genetics significantly contributes to the clinical outcome of HBV infection. NTCP plays an important role in the enterohepatic circulation of bile acids and also serves as a receptor for hepatitis B and D viruses . However, a previous study has reported that common variants in NTCP might not influence the expression level of SLC10A1 at transcriptional regulation, hence may not be associated with HBV susceptibility .…”
Section: Introductionmentioning
confidence: 98%
“…However, the distribution of the minor allele was not in accordance with the Hardy-Weinberg equilibrium (p<0.001), due to less individuals being homozygous for S267F than the expected value. A study of limited number of subjects showed that in the Chinese Han population the S267F variant was associated with HBV infection (OR 2.91 (95% CI 1.10 to 7.74), p=0.03)19; while a larger cohort study of 1899 patients with HBV showed that S267F was associated with resistance to CHB (OR (95% CI) 0.36 (0.29 to 0.44) and 0.16 (0.06 to 0.40) for heterozygotes and homozygotes, respectively) 20. Our results showed that S267F AA homozygotes were strongly associated with HBsAg-seronegativity (OR 0.13 (95% CI 0.05 to 0.34), p<0.001), which support the findings of the later report.…”
Section: Discussionmentioning
confidence: 99%
“…Previous association studies on NTCP S267F and HBV infection have yielded conflicting results,19 20 and the role of this variant in cirrhosis and HCC remains unclear. In addition, no studies have focused on identifying genetic variants in the key functional region between aa157 and 165 of NTCP among patients with CHB.…”
Section: Introductionmentioning
confidence: 97%
“…Substitution of a phenylalanine for a serine at position 267 (p.Ser267Phe ( the S267 variant) (c.800G>A, rs 2296651)14 on SLC101A has been identified leading to normal cell-surface expression of NTCP but with complete loss of bile-salt uptake (figure 1). 12 14 15 The S267F allele is found in East Asian populations,13 with a similar prevalence reported in Chinese Americans 16. The importance of the S267F-NTCP variant on the natural history of HBV to date has not been fully established.…”
mentioning
confidence: 80%
“…The importance of the S267F-NTCP variant on the natural history of HBV to date has not been fully established. The first study in Chinese Han individuals16 surprisingly found that the S267F variant was associated with an increased risk of HBV infection; however, in a much larger study of 1899 patients with HBV of similar ethnicity, the S267F allele was associated with resistance to chronic HBV and a lower incidence of acute-on-chronic liver failure 17. Notably, despite its functional effects, S267F heterozygotes and even homozygotes do not have an obvious disease phenotype independent of HBV 15…”
mentioning
confidence: 99%